Water footprint assessment of gold refining: Case study based on life cycle assessment - Wei Chen (Elsevier, 2021)
Gold industry is essential for socioeconomic development while it brings water consumption and severe water pollution. There are few systematic evaluations of environmental impacts related to water generated by the whole life cycle of gold production. In this study, water availability and water degradation caused by gold refining are evaluated by using water footprint (WF) assessment based on life cycle assessment in order to provide insights for water sustainability in gold industry. Uncertainty analysis is also conducted based on Monte Carlo in order to provide reliable results for decision-making on water management. Results show that carcinogens and non-carcinogens are dominant contributors to the damage category of human health, while freshwater ecotoxicity has dominant contribution to ecosystem quality. In addition, emissions of chromium to water and arsenic to air mainly generated by energy consumption are major contributors to human health, while they are ammonium and copper diffused to water mainly generated by sodium metabisulfite production for ecosystem quality. Results also indicate that energy reduction and energy structure adjustment present significant contributions to mitigate the WF generated by gold production. Finally, recommendations (e.g., promoting the synergetic management of energy and water, optimizing cleaner production index) are proposed to mitigate the impacts associated with water and promote water sustainability in gold industry. More studies such as spatial–temporal analysis should be done to provide helpful reference for decision-making to achieve sustainable development.